2013
DOI: 10.1155/2013/959650
|View full text |Cite
|
Sign up to set email alerts
|

An Elucidation of Neutrophil Functions againstMycobacterium tuberculosisInfection

Abstract: We characterized the functions of neutrophils in response to Mycobacterium tuberculosis (M. tb) infection, with particular reference to glutathione (GSH). We examined the effects of GSH in improving the ability of neutrophils to control intracellular M. tb infection. Our findings indicate that increasing the intracellular levels of GSH with a liposomal formulation of GSH (L-GSH) resulted in reduction in the levels of free radicals and increased acidification of M. tb containing phagosomes leading to the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Infection of PMN with H37Rv strain was performed according to Morris et al [ 16 ] with minor modifications. Briefly, purified PMN were suspended in RPMI 1640 medium supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Infection of PMN with H37Rv strain was performed according to Morris et al [ 16 ] with minor modifications. Briefly, purified PMN were suspended in RPMI 1640 medium supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…However, NAC addition to the culture of M. tuberculosis infected neutrophils caused their killing with an elevation of GSH levels. [ 19 ] Thus, early sputum negativity achieved by NAC could be because of augmented GSH level in macrophages forming S-nitrosoglutathione which may have produced its direct toxicity on bacteria and also decrease in TH2 cytokine response favoring the host immune cells to control the replication of bacteria. Dalvi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies showed that GSH play important role in TB. 8,18,19 Venketaraman V et al showed that H37Rv grown in vitro is sensitive to glutathione (GSH) at physiological concentrations. Data showed that GSH at a 5 mM concentration is bacteriostatic to TB strain H37Rv, suggesting the possibility that the presence of a high concentration of GSH may result in an imbalance in a bacterium containing an alternative thiol for regulating reduction or oxidation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that increasing intracellular levels of GSH with a liposomal formulation of GSH (L-GSH) resulted in reduction in the levels of free radicals and increased acidification of MTB containing phagosomes leading to the inhibition in the growth of MTB. 19 Decreased GSH levels have been shown to activate NFκB, leading to a series of downstream signal transduction events that facilitate TB survival and growth. The low GSH levels in serum of TB infected patients may be a survival mechanism that pathogen employs.…”
Section: Discussionmentioning
confidence: 99%